STRATEGI PESANTREN DALAM MENINGKATKAN KUALITAS SANTRI - Rifaâi, Muh. Khoirul (Dinamika, 2013)
ABTRACTThe strategy of boarding school in increasing the quality of santri. The survival of pesantren/ islamic boarding school is the proudness for moslem, especially pesantren environment. Pesantren/ Islamic boarding school teaches kitab kuning/ yellow books until now, nevertherless most of the people assume that the method is conservative and out of date.This studi aimed to increase the quality of santri in pesantren education as an alternative or model. The effort of PPHM asrama putri (dormitory for female students) sunan pandanaran Tulungagung to increase the quality of santri is based on societal need. Thus, the output of Islamic boarding school (pesantren) competitively in society. Kata Kunci: Strategi Pesantren, Kualitas Santri.